2011
DOI: 10.1016/j.polymertesting.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

On the tension–tension fatigue behaviour of a carbon reinforced thermoplastic part II: Evaluation of a dumbbell-shaped specimen

Abstract: For performing uni-axial fatigue tests on composite materials, the ASTM D3479/D3479M Standard Test Method for Tension-Tension Fatigue of Polymer Matrix Composite Materials is often considered. This standard prescribes a rectangular shaped specimen with end tabs. However, in part I of this study it became clear that for some materials, such as the carbon PPS under study, the proposed geometry is not ideal for fatigue tests. In this manuscript, a dogbone shape is assessed to see whether it performs better under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 19 publications
1
39
1
Order By: Relevance
“…Figure 8 gives an overview of the experiments and it can be noted that the scatter is quite low for these results. Furthermore, there is no frequency dependency, contrary to what was found in [27], where the loading frequency had an influence on the fatigue life of the same carbon PPS under study, but for uni-axial tension-tension fatigue. To have a first idea of what is happening during the fatigue life, the displacement of the specimen is observed using the maximum, minimum and mean values of the measurement.…”
Section: Tension-tension Fatigue Experimentscontrasting
confidence: 79%
See 1 more Smart Citation
“…Figure 8 gives an overview of the experiments and it can be noted that the scatter is quite low for these results. Furthermore, there is no frequency dependency, contrary to what was found in [27], where the loading frequency had an influence on the fatigue life of the same carbon PPS under study, but for uni-axial tension-tension fatigue. To have a first idea of what is happening during the fatigue life, the displacement of the specimen is observed using the maximum, minimum and mean values of the measurement.…”
Section: Tension-tension Fatigue Experimentscontrasting
confidence: 79%
“…As the minimum of the displacement does not increase, there is no permanent deformation. Given the low uniaxial load levels, no permanent deformation of the adherends was expected [27,28], but this means that there is virtually no permanent deformation of the overlap area under shear loads. A little sliding of the specimen in the grips is present, as can be seen at the beginning of the test since the displacement starts at 0 mm, but increases slightly.…”
Section: Tension-tension Fatigue Experimentsmentioning
confidence: 99%
“…For a maximum stress lower than 550 MPa, the material has a lifetime well over one million cycles, which may be considered infinite, whereas for values higher than 600 MPa, the specimen fails after a few dozen cycles. For more fatigue results, the authors refer to [29,2]. …”
Section: Fatigue Experiments On [(0°90°)] 4s Specimensmentioning
confidence: 99%
“…Therefore, the behaviour throughout the fatigue life will be observed more closely in this part of the study. In the second part of this study [2], some improvements to the geometry will be suggested and their effects on the fatigue behaviour will be commented on. Throughout the fatigue lifetime, damage can take many forms in fibre-reinforced composites [3,4,5]: (i) matrix cracks, (ii) fibre-matrix interface failure, (iii) fibre pull-out, (iv) delaminations, (v) fibre fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Residual tensile strength tests are performed with a 100 kN MTS electromechanical testing machine. As proposed by Payan et al and De Baere et al [15,40], a dumbbell shape is used for these specimens (Fig. 8b) in order to keep the failure area away from the specimen tabs and testing machine grips.…”
Section: Residual Tensile Strength Of [0/90] 2s Specimensmentioning
confidence: 99%